2012
DOI: 10.1016/j.febslet.2012.09.004
|View full text |Cite|
|
Sign up to set email alerts
|

Central angiotensin II‐induced Alzheimer‐like tau phosphorylation in normal rat brains

Abstract: Edited by Barry HalliwellKeywords: Angiotensin II Glycogen synthase kinase 3b Tau Alzheimer disease a b s t r a c t Growing evidence suggests that Alzheimer disease (AD) origins in vascular lesions. As the crucial mediator of vascular pathology, angiotensin II-induced significant amyloid production in our laboratory, although amyloid neurotoxicity depended on phosphorylated tau (p-tau) in recent studies. In the present study, p-tau levels were significantly elevated by central angiotensin II via glycogen synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 37 publications
2
72
2
Order By: Relevance
“…In an animal study, infusion of angiotensin II into the brain parenchyma increased the production of p-tau through activation of glycogen synthase kinase 3 ␤ (GSK 3␤), the main tau kinase [17]. We found that anti-AT1R levels in serum correlated significantly with both CSF t-tau and CSF p-tau.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In an animal study, infusion of angiotensin II into the brain parenchyma increased the production of p-tau through activation of glycogen synthase kinase 3 ␤ (GSK 3␤), the main tau kinase [17]. We found that anti-AT1R levels in serum correlated significantly with both CSF t-tau and CSF p-tau.…”
Section: Discussionmentioning
confidence: 88%
“…Even though increased anti-AT1R levels do not seem to affect AD progression, they could contribute to an enhanced risk for AD by damaging the cerebral microcirculation, increase neuroinflammation, or penetrate into the brain parenchyma and activate tau kinases [17]. Once AD is clinically detectable, driving forces in the brain might be too strong to be influenced by a functional autoantibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the angiotensin system increases the permeability of the BBB, induces oxidative stress in the microcirculation of the brain, and leads to an increase in A and tau pathologies [26]. Therefore, we investigated whether resveratrol affects AT1R signalling in the AD.…”
Section: Admentioning
confidence: 99%
“…Most of the deleterious effects of the brain RAS in AD are believed to be associated with elevated Ang-II levels and its subsequent over-activation of angiotensin receptor type-1 (AT1R), commonly referred to as the classical axis of RAS (reviewed in [5]). Infusion of Ang-II increased both amyloid-beta (Aβ) (via increased amyloidogenic processing of APP) and tau pathology, and reduced cognitive performance in ageing Sprague Dawley rats [6,7]. We have previously reported that angiotensin-converting enzyme-1 (ACE-1), the rate-limiting enzyme in the production of Ang-II, is increased in AD in human brain tissue [8,9].…”
Section: Introductionmentioning
confidence: 99%